Semiotika Visual Patung Monumen Tuanku Imam Bonjol Kota Bukittinggi - Asra Ilal Khairi; Dwi Mutia Sari; Siti Aisyah; Zubaidah Zubaidah (Mathematics Education Study Program, 2025)
The monument was erected to commemorate an important event. In the archipelago there are monuments spread across many regions in Indonesia, one of which is in Bukittinggi City, namely the Tuanku Imam Bonjol monument. The main purpose of the construction of the Tuanku Imam Bonjol monument is to commemorate and commemorate the war struggle of the priests against the colonizers. This monument is a symbol of unity and pride for the Minangkabau people in particular, the existence of this monument is now not noticed by the people in Bukittinggi City, especially young people, let alone to understand the visual meaning embedded in the monument, they do not even understand the existence and events that occurred during the Padri War in the early 1800s. This research is important to be carried out as an effort to explore information and notifications regarding the value and meaning conveyed through visual semiotics. The research was carried out in Bukittinggi City with a qualitative type of research through a descriptive approach. Based on this research, it was found that the shape of the Tuanku Imam Bonjol monument consisted of the base of the monument, the posture, and the figure of Tuanku Imam Bonjol who was riding a horse with the front position of the horse's legs raised both, the semiotics in this pose depicted the fighting spirit of upholding sharia in customs and community life. The function of the Tuanku Imam Bonjol Monument is as an image of the Minangkabau community.